Boy on a horse : the story of Adam Lindsay Gordon - Samuel, H. J. (Helen Jo) (Cheshire, 1957)
The story of the poet, Adam Lindsay Gordon, who was, in his day, considered one of Australia's great poets and whose work earned him a memorial in the Poet's Corner of Westminster Abbey.